Anticoagulation and Antithrombotic Therapy in Atrial Fibrillation - Rizzo, Toni (MD Conference Express, 2012)
Patients with atrial fibrillation (AF) have a 5-fold risk of stroke and suffer more severe strokes compared with the general population [Camm AJ et al. Eur Heart J 2010]. One-year mortality in stroke patients with AF is 63% versus 34% in those without AF (p<0.001) [Lin H-J et al. Stroke 1996]. The risk of stroke recurrence is slightly higher in patients with AF (6.9% vs 4.7% in those without AF; p=0.0398) [Marini C et al. Stroke 2005].